ECOLOGICAL ROLE OF ANIMAL DIVERSITY IN SOIL SYSTEM (A CASE STUDY AT EL- RAWAKEEB DRY LAND RESEARCH STATION, SUDAN) - Maha Ali Abdel Latif (European Scientific Journal, ESJ, 2013)
Interest in soil biodiversity characterization and its function in soil ecosystem have come from the need to develop this ecosystem and manipulate soil biota to encourage a greater reliance on ecosystem self-regulation. Observations on the impacts of agricultural managements on populations and communities of soil fauna and their interactions confirm that high input, intensively managed systems tend to promote low diversity while lower input systems conserve diversity. Animal diversity contributes to soil ecology and functioning such as breakdown and cycling of nutrients in the soil. These animals are essential to the proper function of the soil ecosystem in different environments. In arid environment, the role of soil Collembola , mites and nematodes in decomposing plant litter was assessed and compared in El-Rawakeeb Dry land Research Station, (latitudes 15" - 2ᵒ and 15"- 36ᵒ N and longitudes 32" -0ᵒ and 32" – 10ᵒ E) as affected by application of organic manure (bovine manure) or pesticide ( neem leaf powder) over one year. Thirty litter bags each one contain 10 gm oven dried litter of Cajanus, cajan were buried into the treated and control plots. Six bags per plot along with their respective soil were retrieved four times the year. Mean mass loss in litter was correlated to population density of Collembola, mites and nematodes. Some soil properties eg. temperature, moisture , particle size distribution and organic matter contents were correlated to litter mass loss. Results showed that manuring enhanced role of decomposers in decomposing plant litter, while neem application mostly retarded it.